Concurrent occurrence of adenoid cystic carcinoma of the salivary glands with small cell carcinoma of the liver: A rare case report - Premkumar, Jeyanthi (Medknow Publications & Media Pvt Ltd, 2013)
Adenoid cystic carcinoma (ACC) is a clinically deceptive and histologically specific malignancy of salivary gland origin. It is the most common minor salivary gland malignancy. Small cell carcinoma (SCC) is a type of undifferentiated malignant neuroendocrine tumor reported rarely in the liver. Though there are many reported cases of SCC involving liver and ACC of minor salivary glands, the review of literature does not show any reports of concomitant occurrence of these two tumors. We describe a rare case of ACC of the oral cavity and its coexistence with a SCC involving liver, identified and confirmed by histological, and immunohistochemical observations. To our knowledge, this is the first reported case of an ACC of the oral cavity and SCC of liver occurring concomitantly in the same patient.